Analysis of errors in learners' written dialogues responses - Basiron, Halizah; Knott, Alik; Robins, Anthony (2009)
In Malaysia, English is the second most important language after Malay language (L1). Although students have learnt English for at least eleven years in schools, they are still having difficulties in acquiring or comprehending the language. This paper presents results of error analysis of language learners in written language learning dialogues. The corpus of written data was collected from 173 lower secondary students' schools in Malaysia. We created our own error classification scheme and used it as a guideline to check the corpus data. The error classification scheme covered 6 categories of errors and had 15 error codes. The error analysis results answer two research questions: “What are the most common errors made by students?” and “How does performance of the students change over time?” We found out that the most common errors made are an absence of determiners and of the copula “be” in students' sentences. The incorrect use of verb tense is the second most common error. One possible explanation for this problem is an interference of grammar rules between L1 and English. Therefore there is a suggestion for language teachers to perform a comparative analysis between both languages. In response to the second question, we have a hypothesis that “The proficiency of higher form students should be greater than proficiency of lower form students”. Statistical tests were performed to find the answer. The results proved that there is a significant difference between the higher and lower form level groups. Overall this means the students performed better as they went through language learning process over time. However, there are some interesting exceptions to the results when we applied statistical tests to each type of errors. Results showed that there are some grammar constructions that the higher level group is still not improving upon. Those constructions are the use of determiners and the copula, and subject verb agreement rules. Some factors that may contribute to the problem have been outlined. The contributory factors are L1 interference, inconsistency of the provision of error feedback, insufficient time spent for grammar teaching and learning, and insufficient exposure to proper English usage.